Implementasi Model Pembelajaran Berbasis Masalah dan Pengaruhnya terhadap Perkembangan Karakter Mahasiswa - Supriadi Supriadi; Wildan Wildan; Dwi Laksmiwati (Jurnal Penelitian Pendidikan IPA, 2020)
The purpose of this study was to describe the implementation of problem-based learning in environmental chemistry course and its effect on the development of students’ character at Chemistry Education Programe, FKIP, Mataram University in the even semester of 2019/2020. This research was a pre-experimental research with pre-test post-test design, using a class consisting of 31 students. During class discussions, each group was very active in responding and defending opinions based on the references they had in the form of books, journals, and papers that they obtained from various sources. After being analyzed using the ANOVA test, an average score (mean) of students' characters after learning was 239.03 significantly higher than the mean before learning of 219.58. The character component includes attitudes, interests, values, and self-concepts significantly contribute to student character.